Double resource optimization for a robust computer network subject to a transmission budget - Lin, Yi-Kuei; Chen, Shin-Guang (Annals of operations research, 2016)
To maintain a reliable computer network is now a challenge in our daily business operations especially when the transmission budget is limited. A computer network usually consists of transmission lines and transmission facilities, both of which may suffer failure, partial failure, or be in maintenance. Such a computer network is called a stochastic-flow network, since both kinds of resources are stochastic in nature. The problem of double resource optimization for a robust computer network subject to a transmission budget (DROCNTB) is to search for the exact minimum double-resource assignments under transmission-budget constraint such that the computer network keeps survived even under both kinds of failures. This paper develops an efficient algorithm to search for the exact optimal assignment for the DROCNTB problem. Several benchmark examples are explored and compared. The results show that the proposed algorithm is very efficient.